A note on the interaction of spontaneous and evoked release at the frog neuromuscular junction - Barrett, Ellen F. (1974)
1. The interaction between spontaneous miniature end-plate potentials and evoked end-plate potentials was investigated at the frog neuromuscular junction using focal extracellular recording techniques. 2. End-plate potentials evoked immediately after a spontaneous miniature potential were facilitated by up to 20%. The percentage facilitation was negatively correlated with the average quantal content of the end-plate potential.